Beyond Zen: D. T. Suzuki and the Modern Transformation of Buddhism - Blum, Mark L.; Breen, John; Breen, John; Dobbins, James C.; Freeman, Alice; Sueki, Fumihiko; Jaffe, Richard M.; Rosenbaum, Roman; Shields, James Mark; Yamada, Shōji; Snodgrass, Judith; Starrs, Roy; et al. (University of Hawaii Press, 2022)
Beyond Zen: D. T. Suzuki and the Modern Transformation of Buddhism is an accessible collection of multidisciplinary essays, which offer a genuinely new appraisal of the great Zen scholar-practitioner, D. T. Suzuki (1870-1966). Suzuki's writings and lectures continue to exert a profound influence on how Zen, Buddhism more broadly, and indeed Japanese culture as a whole, are understood in the U.S., Europe, and across the globe. With the publication of Beyond Zen, we have at last in a single volume a comprehensive assessment of Suzuki that locates him and his legacy in the context of the turbulent age in which he lived. Now is the perfect moment for reflection and stock-taking. The fiftieth anniversary of Suzuki's death passed just a few years ago, the copyright on his literary output has expired, and his selected works have recently been published by a major American university press.The work comprises twelve essays by some of the best Zen scholars in the world, Anglophone and Japanese, seasoned and young. They take a fresh look at Suzuki, his life and legacy, and their themes range broadly. Readers will find here explorations of Suzuki as he engaged with Zen and Mahāyāna Buddhism; nationalism and international relations; war and peace; religion, literature, and the media; the individual and society; and family, friends, and animals. Beyond Zen is structured chronologically to reveal the development in Suzuki's thought during his long and eventful life. All in all, this collection offers a compelling, provocative, and multidimensional reappraisal of an extraordinary man and his times